A prospective, longitudinal, observational study to assess the health-related quality of life of patients with pancreatic ductal adenocarcinoma in the South African context - Kotze, Urda Karin (Division of General Surgery, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive visceral malignancy originating from pancreatic duct cells. Despite advances in detection, diagnostic procedures and surgical and oncologic treatment, the overall prognosis remains dismal. GLOBOCAN 2020 ranks PDAC as the 7 th leading cause of all cancer deaths. There are no reliable statistics on the incidence of PDAC in South Africa. The National Cancer Registry South Africa of 2017 reports that PDAC accounts for 0.53% and 0.58% of all cancers in females and males respectively. However, this low incidence may be due to underreporting, as the diagnoses are based on positive histology which are performed on only a small proportion of PDAC patients reported by the National Health Laboratory Service (NHLS), only one of several laboratories in South Africa. The overall 5-year survival rate for all PDAC patients is reported to be less than 5%, and the overall median survival is 4-7 months from the time of diagnosis. Surgical resection offers the only chance of cure, but as few as 10% of patients are treated with curative intent with 5-year survival rates of 15-25%. A median survival of 2.8-5.7 months has been reported for patients with metastatic disease. Early symptoms of PDAC such as loss of appetite, weight loss and fatigue are vague and non-specific, which often leads to a delay in the diagnosis. Approximately 80% of patients who have PDAC involving the head of the pancreas present with painless jaundice. In those with advanced disease other digestive symptoms such as loss of weight, nausea and vomiting, bloating, altered bowel habits and backache are prominent. Because of the severity of symptoms, the small proportion of patients who are eligible for curative treatment, and the dismal overall survival, palliative treatment is an important component of the overall treatment of PDAC. In this respect information provided by health-related quality of life (HRQOL) assessments, which refer to the subjective experiences and perceptions of patients regarding their health, illness, and medical interventions, and how these affect their everyday life and functioning, are invaluable for planning and assessing the effect of palliative treatment. HRQOL assessment quantifies not only the actual symptoms but also the effect of the disease on a person in his or her totality. Many studies that report on HRQOL in PDAC are conducted in sponsored clinical trials and are guided by regulatory requirements. These studies typically include highly selected cohorts defined by strict inclusion and exclusion criteria, and results do not reflect HRQOL in the larger unselected patient population. Several nonclinical trial PDAC HRQOL studies have been done both in patients who underwent an operation and those who received palliative treatment. The prognostic value of HRQOL parameters have also been investigated. Very little data are available on the HRQOL of PDAC patients in low- and middle-income countries (LMICs), and to our knowledge no data have been published on the HRQOL of PDAC patients in South Africa. The aim of this research was to assess HRQOL in a South African PDAC patient cohort presenting at a major hepato-pancreato-biliary (HPB) academic referral centre, and to determine the possible clinical applications of HRQOL outcomes in the management of these patients, treated with either curative or palliative intent. The European Organisation for Research and Treatment of Cancer (EORTC)-QLQ-C30 and EORTC-QLQ-PAN26 instruments were used in a longitudinal design study to allow for comparisons with baseline (BL) reports at regular intervals, thereby identifying statistically significant and clinically meaningful changes that may have occurred over time. As in previous publications, a high mortality and decreasing compliance over time in both the curative intended and palliative cohorts were noted. In contrast to patients who underwent an operation in whom the functional and symptom scales and scores fluctuated notably between time points, the same remained relatively stable in the patients who received palliative treatment. Some interesting observations regarding the possible prognostic value of HRQOL outcomes in the respective treatment groups need to be further investigated in larger patient cohorts. Some of the lessons learnt in this study from a LMIC, may be of value in planning subsequent tumour-related HRQOL studies in LMICs, regardless of tumour type.